Comparison of ondansetron, tropisetron, and palonosetron for the prevention of postoperative nausea and vomiting after middle ear surgery - Ahmet Aydin, MD; Mustafa Kaçmaz, MD; Adem Boyaci, MD (Elsevier, 2019)
ABSTRACT: Background: Postoperative nausea and vomiting (PONV) are 2 of the most frequent adverse effects of anesthesia. PONV prolongs hospital stays and also delays the recovery of patients. Objective: In this study, the effects of ondansetron, tropisetron, and palonosetron on PONV in patients who had undergone middle ear surgeries such as mastoidectomy or tympanoplasty were compared. Methods: The study included 165 American Society of Anesthesiologists grade 1 and 2 patients aged 18 to 65 years. Patients were randomized into 3 groups by a closed envelope method. Neither the patients nor the nurses administering the treatments knew which patient belonged to which group. The anesthetic technique was standardized for all groups. During skin closure, 0.075 mg palonosetron, 5 mg tropisetron, and 8 mg ondansetron were administered intravenously to the palonosetron, tropisetron, and ondansetron groups, respectively. After completion of the surgery, the patients were followed for 48 hours. Diclofenac sodium (100 mg IM) was administered to patients experiencing pain and metoclopramide chloride (10 mg IM) was administered to patients with nausea or vomiting. Potential side effects such as headache and constipation were recorded in the postanesthesia care unit and ear, nose, and throat clinic. Results: There was no significant difference in the effects of all 3 antiemetic agents on the severity of PONV (P = 0.081). At 48 hours postoperatively, the incidence of PONV was significantly lower in the palonosteron group (38.2%) than the ondansetron group (63.6%) and tropisetron group (61.8%) (P = 0.011). At 48 hours postoperatively, the incidence of postoperative nausea was significantly lower in the palonosetron group (32.7%) than in the ondansetron group (63.6%) and the tropisetron group (56.4%) (P = .003). The incidence of PONV between hours 12 and 24 postoperatively was significantly higher in the ondansetron group (27.3%) than in the palonosetron group (9.1%) (P = 0.013). The antiemetic requirement in the first hour after surgery was significantly higher in the tropisetron group (25.5%) than in the palonosetron group (7.3%) (P = .019). Conclusions: The results of the current study support those of earlier studies that suggest that palonosetron was statistically more effective than the other 2 formulations in the prevention of PONV in patients who have undergone middle ear surgery. (Curr Ther Res Clin Exp. 2019; 80:XXXXXX). Key words: Ear, Nausea, Ondansetron, Palonosetron, Tropisetron, Vomiting, Classification: sex, age, height, weight, American society of anaesthesiologists score, Postoperative nausea and vomiting scoring system